Synthesis of glass-based catalysts for biodiesel production from a blend of beef tallow and waste cooking oil - M. Mashamba; L. Tshuma; L.B. Moyo; N. Tshuma; G.S. Simate (Cleaner Chemical Engineering)
The perennial disparity between supply and demand of energy as a result of burgeoning populations, expeditious urbanisation and industrialisation has driven the need for alternative energy sources. Biodiesel has emerged as a promising vehicular fuel due to its similar physiochemical properties to mineral diesel and its potential to minimise environmental impact. However, the commercialisation of biodiesel production faces challenges, particularly related to feedstock and catalyst selection. This study explored the utilisation of waste laboratory glass to synthesize heterogeneous catalyst for producing biodiesel from a blend of beef tallow and waste cooking oil. Heterogeneous catalysts are crucial for achieving high conversion efficiency, reusability, ease of separation and minimal environmental degradation. The particle size distribution of the catalysts was heterogeneous, with 23.33 % of particles passing 710 μm, 30.83 % passing 500 μm, and 45.83 % passing 350 μm. XRF analysis revealed that silica was the primary elemental constituent, comprising over 70 % of the total sample composition, and successful incorporation of Na, Mg, and Zn in the respective treated catalysts was observed. FTIR analysis of the calcined and uncalcined catalysts showed a sharp decrease in hydroxyl functional groups, indicating successful calcination. All glass-based catalyst samples exhibited strong Si-O-Si vibration stretches around 1100cm−1, confirming the presence of silicon as the glass precursor. The FTIR results of the crude biodiesel samples produced by the catalysts at 15 min intervals showed that the NaOH treated glass-based catalyst exhibited the fastest transesterification reaction.. The results showed that the NaOH treated, MgO treated, Zncl2 treated, and control glass-based catalysts achieved catalyst yields of 80.63 %, 86.13 %, 91.38 %, and 94.25 % respectively, upon calcination. Furthermore, the produced biodiesel was characterised to evaluate its fuel properties: the tested parameters kinematic viscosity, density, flash point and acid value were within the desirable limits for biodiesel according to American and European standards . Moreover, the catalyst showed that it can be reused as after six cycles of reuse a biodiesel yield above 89 % was realised.